SALE OF DRUGS IN SYSTEM WITH SELF PHARMACIES USING MICROSOFT VISUAL BASIC 6.0 - Wulandari Wulandari; Ristyawati Ristyawati, SKom, MMSI (Jurnal Sistem Informasi, 2008)
Pharmacies Kencana Mandiri is an enterprise which handles sales of medicines andservices to buyers both from the Clinic Kencana Mandiri and buyers from outside.For each request and expense of drugs, such pharmacies must keep records and drugcalculations, returns and sale of drugs.Settlement process for recording and calculations are still using manual systems, sothis became one of the causes delays sale of drugs.Based on the above, we need a computerized system and appropriate to support itsdevelopment efforts and increase drug sales process, the system is proposed in orderto overcome problems or constraints on the system is running on PharmaciesKencana Mandiri.